Elaboración y aplicación de una guía didáctica de cuentos pictograficos “Chanita me cuenta” para el desarrollo del lenguaje oral de los niños y niñas de 2 a 3 años del centro infantil del buen vivir “Francisco Chiriboga” de la Parroquia Velasco, Provincia Chimborazo, período 2014 – 2015. - Ruiz Cárdenas, Sandra Elizabeth (2016)
The research topic is "Development and implementation of “Chanita me Cuenta” didactic guide of pictographic tales for oral language development of boys and girls from 2 to 3 years of Early Childhood Center of Good Living “Francisco Chiriboga” from Velasco parish, Chimborazo province, period 2014-2015. This research work was carried out with the purpose to make public the pictographic tales; it will allow relating playful activities for oral language development in the boys and girls, with the direct engagement of parents, teachers, and directors of the institution which facilitate the implementation to put into practice in their daily work. It is a fundamental element so that, in the future, they can reason and interpret pictographic tales, in this way, it understands that human being also have another way to communicate, being the Universal means of strike up a conversation. It is an essential part of the playful activities, which begins through a simple conversation between the boy, the girl, and the adult; it is also very important to understand that words can be transformed into something rewarding to create a tale. It is a didactic resource of great formative importance for children, since through this their abilities and skills are strengthened. The purpose of this research is to present a set of tales divided into three thematic blocks: Block 1, Traditional Tale; Block 2, Narrative Tales; Block 3, Myths and Legends Tales for the improvement of oral language. Communication is one of the essential parts of human beings because it can transmit thoughts, ideas, feelings, etc. The work done in the early years of life develops, determines very important aspects in the future life of infants; for this reason it is necessary to show significant and innovative learning activities, that become the main tool for acquiring the knowledge taught. Therefore, after application of the didactic guide of pictographic tales called "Chanita me cuenta", it has confirmed the positive, direct influence in oral language development.